2017
DOI: 10.1111/all.13356
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life is significantly impaired in nonallergic rhinitis patients

Abstract: These results demonstrate a significant impairment in both AR and NAR patients in their QoL combined with a low treatment satisfaction, emphasizing the need for adequate treatment, especially in the NAR patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 22 publications
0
26
0
4
Order By: Relevance
“…Moreover, we have not always been able to decide among us what the most relevant outcome measures are for different diseases (27) . Quite often we still encounter unvalidated outcome measures, such as SNOT scores used in rhinitis, or validated outcome measures still have to be developed (28,29) . For rhinosinusitis, an outcome measure set was recently developed using an e-Delphi process allowing 110 patients and healthcare practitioners to individually rate outcomes in terms of importance and core outcomes for trials of interventions: CHronic Rhinosinusitis Outcome MEasures (CHROME) (12,30) .…”
Section: Delivering Better Results For Patients Through Core Outcomesmentioning
confidence: 99%
“…Moreover, we have not always been able to decide among us what the most relevant outcome measures are for different diseases (27) . Quite often we still encounter unvalidated outcome measures, such as SNOT scores used in rhinitis, or validated outcome measures still have to be developed (28,29) . For rhinosinusitis, an outcome measure set was recently developed using an e-Delphi process allowing 110 patients and healthcare practitioners to individually rate outcomes in terms of importance and core outcomes for trials of interventions: CHronic Rhinosinusitis Outcome MEasures (CHROME) (12,30) .…”
Section: Delivering Better Results For Patients Through Core Outcomesmentioning
confidence: 99%
“…The effect of NAR on quality of life was first studied only recently . HRQoL in NAR patients was at least equally impaired compared to AR when investigated using a rhinitis‐specific questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have assessed HRQoL in rhinologic patient groups other than CRS and AR. Non‐allergic rhinitis (NAR) is as common as allergic rhinitis, but only one study previously evaluated HRQoL in NAR . This recent study demonstrated a diminished HRQoL amongst NAR patients using a rhinitis‐specific questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…A significant QoL impairment was found in both AR and NAR patients combined with a low treatment satisfaction, emphasizing the need for adequate treatment, especially in the NAR patient group. 83 US swimmers have a higher prevalence of rhinitis than the general population. A questionnaire-based study assessed the prevalence of rhinitis in elite and nonelite swimmers, other athletes, and the general population, focusing on the swimming performance and QoL of the participants.…”
Section: Pre Valen Ce Of Allerg I C Rhinitismentioning
confidence: 96%